A critical analysis on consumption behavior and future projection of print media: a business case of The Daily Star BD - Tajrian, Shamima (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.